2008
DOI: 10.1152/jn.90405.2008
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Specificity of NOP Opioid Receptors to Pertussis-Toxin-Sensitive Gα Proteins in Adult Rat Stellate Ganglion Neurons Using Small Interference RNA

Abstract: The opioid receptor-like 1 (NOP or ORL1) receptor is a G-protein-coupled receptor the endogenous ligand of which is the heptadecapeptide, nociceptin (Noc). NOP receptors are known to modulate pain processing at spinal, supraspinal, and peripheral levels. Previous work has demonstrated that NOP receptors inhibit N-type Ca2+ channel currents in rat sympathetic stellate ganglion (SG) neurons via pertussis toxin (PTX)-sensitive Galphai/o subunits. However, the identification of the specific Galpha subunit that med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Previous studies have shown that NOP receptors are natively expressed in SG neurons (Ruiz-Velasco et al, 2005;Margas et al, 2008). Thus, this model system was ideal to compare the effects of antagonists or Na ϩ ions under conditions in which NOP receptors are silent (i.e., physiological expression levels) or constitutively active (i.e., high expression levels) within a neuronal environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that NOP receptors are natively expressed in SG neurons (Ruiz-Velasco et al, 2005;Margas et al, 2008). Thus, this model system was ideal to compare the effects of antagonists or Na ϩ ions under conditions in which NOP receptors are silent (i.e., physiological expression levels) or constitutively active (i.e., high expression levels) within a neuronal environment.…”
Section: Discussionmentioning
confidence: 99%
“…SG neurons were isolated from adult rats using the method described previously (Margas et al, 2008). In brief, male Wistar rats (125-175 g) were first anesthetized with CO 2 and then decapitated with a laboratory guillotine.…”
Section: Sg Neuron Isolationmentioning
confidence: 99%
“…Similar to opioid receptors, NOP receptors have been shown to couple to pertussis toxin-sensitive G i/o proteins to inhibit adenylate cyclase, activate inwardly rectifying potassium channels and inhibit calcium channels (Ma et al, 1997;Margas et al, 2008). However, unlike opioid receptors, NOP receptors can also couple to pertussis toxin-insensitive G proteins, including G z , G 16 and G s (Chan et al, 1998;Klukovits et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In one set of experiments (see Fig. 2E), the brain and stellate ganglion (SG) tissue were isolated (Margas et al 2008) and used as a positive control for G␣ i1 and G␣ O protein detection, respectively.…”
Section: Methodsmentioning
confidence: 99%